An overview of alcohol and tobacco/nicotine interactions in the human laboratory. (4th March 2017) - Verplaetse, Terril L.; McKee, Sherry A.
ABSTRACT: Background : Alcohol use disorders and tobacco use contribute significant risk to the global burden of disease, and each are major public health concerns. Together, alcohol and tobacco use are highly comorbid and have multiplicative health risks when used concurrently, underscoring the importance of examining alcohol-tobacco interactions in the human laboratory. Objective : The aims of this review were to summarize the state of research examining alcohol-tobacco interactions in the human laboratory. Methods : We reviewed human laboratory evidence for alcohol and tobacco/nicotine interactions, including 1) craving in drinkers and smokers exposed to smoking or drinking cues, 2) fixed-dosing of alcohol or nicotine in smokers and drinkers, and 3) smoking and alcohol influences on self-administration behaviors. The interactive effects of tobacco/nicotine with other drugs of abuse are also briefly discussed. Results : Overall, results identified that alcohol and tobacco have reciprocal influences on potentiating craving, subjective responses to fixed-dose alcohol or nicotine administration, and self-administration. The literature identified that alcohol increases craving to smoke, decreases time to initiate smoking, and increases smoking self-administration. Similarly, tobacco and nicotine increase alcohol craving, decrease subjective effects of alcohol, and increase alcohol consumption. Conclusion : Future studies should continue to focus on alcohol and tobacco/nicotine interactions in individuals with a wide scope of drinking and smoking histories, different states of alcohol and nicotine deprivation, and influences of either drug on craving, subjective responses, and consumption over the course of the blood alcohol curve. This work could have important implications for the impact of alcohol-tobacco interactions on guiding clinical practice, as well as in the changing landscape of addiction.